Solvothermal Synthesis of Lanthanide‐doped NaYF4 Upconversion Crystals with Size and Shape Control: Particle Properties and Growth Mechanism. Issue 2 (28th December 2020) - Sun, Chunning; Schäferling, Michael; Resch‐Genger, Ute; Gradzielski, Michael
Abstract: Lanthanide‐doped NaYF4 upconversion nano‐ and microcrystals were synthesized via a facile solvothermal approach. Thereby, the influence of volume ratios of ethylene glycol (EG)/H2 O, molar ratios of NH4 F/RE 3+ (RE 3+ represents the total amount of Y 3+ and rare‐earth dopant ions), Gd 3+ ion contents, types of activator dopant ions, and different organic co‐solvents on the crystal phase, size, and morphology of the resulting particles were studied systematically. A possible formation mechanism for the growth of crystals of different morphology is discussed. Our results show that the transition from the α‐ to the β‐phase mainly depends on the volume ratio of EG/H2 O and the molar ratio of NH4 F/RE 3+, while the morphology and size could be controlled by the type of organic co‐solvent and Gd 3+ dopant ions. Furthermore, the reaction time has to be long enough to convert α‐NaYF4 into β‐NaYF4 during the growth process to optimize the upconversion luminescence. The formation of larger β‐NaYF4 crystals, which possess a higher upconversion luminescence than smaller particles, proceeds via intermediates of smaller crystals of cubic structure. In summary, our synthetic approach presents a facile route to tailor the size, crystal phase, morphology, and luminescence features of upconversion materials. Abstract : The evolution of lanthanide‐doped NaYF4 upconversion crystals under solvothermal conditions is reported.